2016
DOI: 10.21077/ijf.2016.63.3.58881-04
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of fishing on Indian mackerel Rastrelliger kanagurta (Cuvier, 1816) in Tuticorin, south-east coast of India

Abstract: Fishery of the Indian mackerel Rastrelliger kanagurta (Cuvier, 1816) from Tuticorin was studied for the period 2011-2014. Indian mackerel formed fishery round the year in Tuticorin with peak during June to November in trawl and October to December in gillnet. The annual catch varied from 1650 to 5101 t (average 2968 t) in gillnet and from 815 to 1716 t (average 1231 t) in trawl. Total length (TL) of the fishes ranged from 10 to 30.5 cm. Length-weight relationship estimated was W = 0.0038777 * L 3.3 (r 2 = 0.99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The crustacea main components were copepods. 16 We take a picture that the appearance of sand substance was grainy texture and for copepods it was brownish. The pictures are presented in the Figure 1 and Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The crustacea main components were copepods. 16 We take a picture that the appearance of sand substance was grainy texture and for copepods it was brownish. The pictures are presented in the Figure 1 and Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…(Bhendarkar et al, 2018) [9] found the absolute frequency ranged between 55,264 to 3,24,568 eggs with an average of 1,08,266 and (Rao,2009) 20,911 to 1,11,000 eggs and 39,600 to 73,781 eggs (Pillai, 2009) [11] and Abdussamad et al, (2010) [1] 68,500 eggs, Hulkoti et al, (2013) [6] 86,744 to 94,376 eggs, Arralfi et al, (2016) -24,542 to 1,23,760 eggs.Fecundity estimates of mackerel in earlier studies range (Devanesan and John, 1940) [4] found 94,000 eggs .But (Sekharan, 1958; Yo-hannan and Abdurahiman, 1998) [12] and several researchers felt that fecundity of mackerel is much higher than these reports. Pillai et al (2009) [11] reported that the fecundity of Rastrelliger kanagurta ranged from 39,600 eggs to 73,781.The calculated fecundity of Indian mackerel in Tuticorin coast by Abdussamad et al (2010) [1] was 68,500 eggs. The recent study by Hulkoti et al (2013) [6] obtained fecundity between 86,744 and 94,376 eggs.In 2016 (Arrafi et al,2016) [3] counted the fecundity of R. kanagurta varied from 28,542 to 123,760 eggs.…”
Section: Post Monsoonmentioning
confidence: 99%
“…Due to its simple procedure and it provides good results. Many studies were used the gut content to determine several fishes such as Mugil cephalus, Selene peruviana and Eucinostomus currani (Ramírez-Luna et al, 2008) and Rastrelliger kanagurta (Sivadas & Bhaskaran, 2009). The stomach/gut content analysis was coevaluated by calculating the index of relative importance, IRI to accurately interpret the result from the stomach/gut content.…”
Section: Feeding Ecology Of Fishmentioning
confidence: 99%
“…It is relatively simple procedure and provides good results (Ducommun et al, 2010;Kaifu et al, 2013;Wootton, 2012). A previously described procedure of the gut content was used to determine in several fishes such as Mugil cephalus, Selene peruviana and Eucinostomus currani (Ramírez-Luna et al, 2008) and Rastrelliger kanagurta (Sivadas & Bhaskaran, 2009). In fact, the characterization of the feeding aspect is studied to ensure in parallel to histological aspect.…”
Section: Introductionmentioning
confidence: 99%